Is subscapularis recruited in a similar manner during shoulder internal rotation exercises and belly press and lift off tests?. Issue 6 (June 2017) - Ginn, Karen A.; Reed, Darren; Jones, Chelsea; Downes, Anthony; Cathers, Ian; Halaki, Mark
Abstract: Objectives: Although the belly press and lift off tests are recommended to assess subscapularis function, shoulder internal rotation (IR) exercises performed in other shoulder positions are more commonly used to restore subscapularis function. It is not known if shoulder IR exercises specifically activate subscapularis to the same degree as the lift off and belly press tests, and thus have the potential to effect subscapularis strength gains. Therefore, the aim was to compare subscapularis activation levels with those of other shoulder internal rotator muscles during the belly press and lift off tests and shoulder IR exercise positions. Design: Original research. Methods: Twenty asymptomatic volunteers performed maximal isometric contractions during the belly press and lift off tests and shoulder IR performed at 90° and 0° abduction in an upright position and supported at 90° abduction in supine. Muscle activation levels were recorded using a combination of indwelling and surface electrodes. Data were normalized to maximum voluntary contractions and averaged. Results: Moderate average subscapularis activation levels were recorded during all shoulder IR tasks examined with no significant difference between tasks (p = 0.18). The belly press test was the only IR task in which subscapularis activation levels were significantly higher than all other shoulder internal rotator muscles (p < 0.05). Conclusions: Shoulder IR exercises activate subscapularis to similar moderate levels as the belly press and lift off tests and therefore, have similar potential to strengthen subscapularis. However, the belly press test, with significantly higher subscapularis activation than other shoulder internal rotators, more specifically targets subscapularis.